The challenges of using the Communicative Approach (CA) in the teaching of English as a Second language (ESL) in Zimbabwe: Implications for ESL teacher education - Mutekwa, Anias (Taylor & Francis (Routledge), 2016)
This article examines studies done on the use of the CA locally, in addition to insights from studies done abroad, as well as critically examining the nature of the CA and the language situation in Zimbabwe, to identify and discuss the main challenges associated with the use of this approach to the teaching of ESL in Zimbabwe and its implications for ESL teacher education. It explores the status of the CA as ‘imported technology’, that has been grafted to address the teaching of English as a second language in the local context, necessitating its adaptation and the development of local versions of the approach. It argues that, to address these challenges, various stake holders such as teacher educators, material developers, examination bodies, and other relevant authorities such as the ministry of education should each play their part to ensure the success of the implementation of the CA.